Coloring and size influence preferences for imaginary animals, and can predict actual donations to species‐specific conservation charities. Issue 4 (23rd April 2020) - Curtin, Polly; Papworth, Sarah
Abstract: As conservation has limited funds, numerous studies have identified aesthetic characteristics of successful flagship species which generate donations and conservation. However, prior information about species can also impact human preferences, and may covary with animal appearance, leading to different conclusions about which species will be most effective. To separate these two factors, we use images of imaginary animals as a novel paradigm to investigate preferences for animal appearance in conservation donors. Using discrete choice experiments, we show that potential conservation donors prefer larger imaginary animals which are multicolored and cooler toned. We found no effect of eye position or fur, which we used as a proxy for mammalian species. Furthermore, we demonstrate that these preferences can predict the number of donations received by species‐specific conservation charities. These results suggest coloring, and particularly number of colors, is an overlooked aspect of animal appeal, and an important aesthetic characteristic for identifying future flagship species.